The Impact of Enterprises Open Data Maturity Level on the Attainment of Sustainable Development Goals - Theme Analysis - Blatnik, Staša (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Over the past two decades, open data has become a key element of digital transformation and innovation in enterprises. The Open data in enterprises enables them to grow economically, enhance social responsibility, and engage in environmental sustainability programs. The effective use of open data within organizations enables improved decision-making processes, business optimization, and thus creation of added value. However, a question arises: how does the maturity level of organizations for the use of open data influence the attainment of Sustainable Development Goals (SDGs). This paper provides a comprehensive definition of the problem. With the use of Soft Systems Methodology it analyzes the process, from publishing the open data to its use, for the attainment of SDGs and the various stakeholders involved. This establishes a foundation for further research on how an enterprise’s maturity to use open data impacts the attainment of SDGs.